Pengaruh Rasio Rentabilitas, Rasio Solvabilitas, Rasio Aktivitas, Dan Rasio Likuiditas Terhadap Harga Saham (Studi Kasus Pada Perusahaan Subsektor Property Dan Real Estate Periode 2014-2017) - Widya Sari; Andy Andy; Calista Wongso; Erwin Erwin; M Dicky Zoelkaranain (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2019)
The purpose of this study was to analyze the the influence of Net Profit Margin, Debt to Equity Ratio, Total Assets Turnover, and Current Ratio to Stock Price. The sample of this study was ninety-six financial reports of Property and Real Estate companies which are listed in Indonesia Stock Exchange using a quantitive research method. The multiple regressions analyisis was used as the analysis technique. The study results showed that Net Profit Margin and Total Assets Turnover have significant influence toward Stock Price partially while Debt to Equity Ratio and Current Ratio have no influence toward Stock Price partially.